2021
DOI: 10.1167/tvst.10.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Development of Refractive Error in Children Treated With Intravitreal Bevacizumab or Laser for Retinopathy of Prematurity

Abstract: Purpose To compare the patterns of longitudinal refractive error development during the first 3.5 years in children with severe retinopathy of prematurity (ROP) treated with intravitreal bevacizumab (IVB) or laser photocoagulation. Methods This prospective cohort study enrolled extremely preterm infants (birth weight < 1000 g, gestational age 23–27 weeks) with type 1 ROP from multiple hospitals in Dallas between 1999 and 2017; IVB group (N = 22); laser group (N = 26). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, compared with our study, the study by Young et al 40 not only lacked specific treatment guidance but also had a relatively small sample size. Currently, many studies are investigating the various effects of LP and IVI on infants with ROP, including visual acuity, ocular structure, refractive status, and even neural development 4–7,9–11 . However, these studies are mostly based on clinical data; therefore, the treatment decision of whether to implement LP or IVI for ROP still relies on clinical doctors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with our study, the study by Young et al 40 not only lacked specific treatment guidance but also had a relatively small sample size. Currently, many studies are investigating the various effects of LP and IVI on infants with ROP, including visual acuity, ocular structure, refractive status, and even neural development 4–7,9–11 . However, these studies are mostly based on clinical data; therefore, the treatment decision of whether to implement LP or IVI for ROP still relies on clinical doctors.…”
Section: Discussionmentioning
confidence: 99%
“…LP is a conventional treatment, while IVI were introduced later and offer benefits such as faster regression of ROP lesions without the need for sedation. 4,5 Both treatments have advantages and disadvantages, [6][7][8][9][10] and selection should be made according to the ROP severity. The selection of treatment modalities is important because it affects the outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, since a higher degree of myopia in aggressive posterior ROP than in type 1 ROP [11] was reported in the subgroup analysis, future studies should elucidate whether the observed refractive status in the treated eyes is a function of the treatment modality or protocol or depends on the zone of involvement (The anti-VEGF-treated eyes with posterior ROP developed a significantly lower SEQ compared to the anti-VEGF-treated eyes with peripheral zone II [23]) or stage of ROP (With random allocation of the eyes with stage 2 or 3 ROP to the anti-VEGF or laser treatment group, comparable spherical and cylindrical refractive outcomes were found at a postmenstrual age of 90 weeks [45]), or both. Moreover, the impact of child age factor should be investigated over a long followup, as after 1.1 years, the rate of SEQ change was significantly slower for both treatment modalities [1].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF monotherapy in the eyes treated for severe ROP leads to a lower prevalence of myopia compared to laser treatment. Similarly, lower anisometropia develops after anti-VEGF monotherapy, with similar levels of significant astigmatism between the two treatment modalities [1]. In school children with a history of lasertreated type 1 ROP, the eyes developed a significantly higher degree of myopia compared to those with a history of anti-VEGF monotherapy.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation